Optimizing the SAKTI application to raise reproductive-aged mothers' literacy levels about stunting - JUM NATOSBA (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Stunting is one of the main health issues faced in Indonesia, especially among children under five years old. Based on the 2022 Indonesian Nutrition Status Survey (SSGI) data, the national prevalence of stunting stands at 21.6%, although there has been a decrease compared to previous years. At the provincial level, South Sumatra also faces significant challenges in reducing the stunting rate. Based on SSGI 2022 data, the prevalence of stunting in South Sumatra is at 24.8%, slightly higher than the national average. This community service program aims to increase public understanding of stunting. The method used is Focus Group Discussion (FGD). The results of the activity showed an increase in community knowledge about stunting by 5.35% based on the pre-test and post-test results. These findings indicate that the intervention in the form of education based on the SAKTI application within the community is effective in reducing the risk of stunting. This program is expected to become a model that can be replicated in other villages with similar conditions.